Traffic offending and deterrence: An examination of recidivism amongst drivers in Victoria, Australia born prior to 1975 - Hayley McDonald; Janneke Berecki-Gisolf; Karen Stephan; Stuart Newstead; Quan Yuan (PLoS ONE, 2020)
To deter the performance of illegal driving behaviours, traffic infringement notices may be issued. Whilst there is a substantial body of research that has examined rates of reoffending following a traffic infringement, there have been few studies examining the length of time to next traffic offence. Where this research has been conducted, the findings do not provide current understandings, given the substantial changes in traffic sanctioning over time. The aim of this study was to address this gap, by examining risk factors for recidivism following a driver receiving a traffic infringement notice, as well as the time to next traffic offence. Licensing and infringements data held in the Driver Licensing System (DLS), maintained by the road authority in Victoria, Australia were used. All drivers included in the study were born prior to 1975, and received their first Victorian drivers licence between 1994 and 2016. Data from 203,620 drivers were used. Cox proportional hazards modelling was undertaken to examine factors associated with recidivism within 12 months of receiving a traffic infringement. 131,691 (64.7%) drivers had received at least one traffic infringement in Victoria, Australia since receiving their Victorian driver’s licence. Factors found to be associated with longer time to further traffic offending in the year that followed the first infringement included being female; receiving a first Victorian driver’s licence when aged 45+ years; and being licenced 10+ years. Traffic infringements deter some groups of Victorian drivers, but not others. If drivers are to be deterred from further illegal driving behaviour, it is important other countermeasures are developed and trialled.